Computed tomographic diagnosis of a fracture of the floor of the pelvis in a Thoroughbred foal. (20th June 2022) - Scilimati, Nicola; Schiavo, Stefano; Lauteri, Eleonora; Beccati, Francesca; Angeli, Giovanni; Di Meo, Antonio; Pepe, Marco
Summary: This case report describes the clinical and diagnostic imaging findings, treatment and outcomes of a 15‐day‐old Thoroughbred foal referred for the evaluation of severe left hindlimb lameness of 8 days' duration. Radiographic examination of the left hindlimb and transcutaneous ultrasonographic examination of the pelvis were unremarkable. A computed tomographic (CT) examination was performed to investigate the proximal aspect of the limb and the pelvis; CT scans of the thorax were also acquired. In this case, CT images allowed detection of a closed, slightly displaced, oblique wedge‐like fracture of the left caudal ramus of the pubis and medial ramus of the ischium, allowing an accurate diagnosis to guide appropriate treatment and prognostication. The foal was treated with anti‐inflammatory drugs and box‐rest. A follow‐up by telephone interview with the trainer 3 years later revealed that the horse is in full athletic activity without any residual gait alteration related to the pelvic fracture.